Medicinal Cannabis Use Among People with Obsessive Compulsive Disorder: Changes in Quality of Life After Three Months - Michael T. Lynskey; Alkyoni Athanasiou-Fragkouli; Anne K. Schlag; David J. Nutt (Psychoactives, 2025)
Obsessive–compulsive disorder (OCD) has an estimated prevalence between 1 and 2.3%. Existing treatments may not be suitable or effective for all people with OCD, and there is increasing interest in whether these individuals may benefit from the use of cannabis-based medical products (CBMPs). We document the characteristics of 257 people reporting a diagnosis of OCD within Project T21, a study of medical cannabis patients, and examined whether the use of prescribed cannabinoids improves quality of life. Individuals with OCD were prescribed an average of 2.2 CBMPs, with most products classified as THC-dominant flowers (73.7%). Three months after initiating treatment, there were substantial improvements in quality of life (Cohen’s d = 0.48; 95% CI = 0.29–0.65), general health (Cohen’s d = 0.43; 95% CI = 0.26–0.61), mood/depression (Cohen’s d = 0.85; 95% CI = 0.65–1.04), and sleep (Cohen’s d = 0.61; 95% CI = 0.43–0.79). There was a corresponding reduction in anxiety symptoms among the subsample who completed the GAD-7 (Cohen’s d = 1.14; 95% CI = 0.84–1.44). Eight individuals (5.7%) reported a total of 14 adverse effects, with the majority of these (57%) being described as mild. Given emerging evidence that those with OCD can benefit from CBMPs, coupled with the increased availability of these unlicensed products internationally, there is a need for more research, including clinical trials, to identify those who may benefit most from the use of these medicines.